The Future of Telepsychiatry in India - Ibrahim, Ferose Azeez (Indian J Psychol Med, 2020)
Technology is bringing about a revolution in every field and mental health care is no exception. The ongoing COVID-19 pandemic has provided us with both a need and an opportunity to use technology as means to improve access to mental health care. Hence, it is imperative to expand and harness the tremendous potential of telepsychiatry by expanding the scope of its applications and the future possibilities. In this article, we explore the different avenues in digital innovation that is revolutionizing the practice in psychiatry like mental health applications, artificial intelligence, e-portals, and technology leveraging for building capacity. Also, we have also visualized what the future has in store for our practice of psychiatry, considering how rapid technological advances can occur and how these advances will impact us. There will be challenges on the road ahead, especially for a country like India for instance; the digital divide, lack of knowledge to utilize the available technology and the need for a quality control and regulation. However, it is safe to presume that telepsychiatry will evolve and progress beyond these roadblocks and will fulfill its role in transforming health care. Telepsychiatry will improve the health care capacity to interact with patients and family. The blurring of national and international borders will also open international opportunities to psychiatrist in India, heralding a new wave of virtual health tourism.